2009
DOI: 10.1007/978-1-4419-1399-9_74
|View full text |Cite
|
Sign up to set email alerts
|

Function and Mechanism of CNTF/LIF Signaling in Retinogenesis

Abstract: Ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF) exhibit multiple biological effects in the developing vertebrate retina. CNTF/LIF inhibits rod photoreceptor, and promotes bipolar cells and Muller glia differentiation. In addition, CNTF/LIF has been shown to have proliferative and apoptotic effects. Moreover, LIF also inhibits retinal vascular development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Indeed, the silencing of PTPIP51 expression did not affect the generation of the CRX-positive photoreceptor precursors. This is in agreement with the down-regulation of PTPIP51 expression in P0 retinal explants treated with ciliary neurotrophic factor (Roger et al, 2007), where an inhibition of the rod photoreceptor differentiation was observed (Ezzeddine et al, 1997;Schulz-Key et al, 2002;Rhee et al, 2004;Rhee and Yang, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the silencing of PTPIP51 expression did not affect the generation of the CRX-positive photoreceptor precursors. This is in agreement with the down-regulation of PTPIP51 expression in P0 retinal explants treated with ciliary neurotrophic factor (Roger et al, 2007), where an inhibition of the rod photoreceptor differentiation was observed (Ezzeddine et al, 1997;Schulz-Key et al, 2002;Rhee et al, 2004;Rhee and Yang, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, abnormal photoreceptor cell death or retinal injury results in reactive gliosis (Fisher and Lewis, 2003; Frasson et al, 1999), which is detected in Pten mutant retinas. Reactive Müller glial cells are known to secret growth factors such as LIF (Joly S, 2008), a member of the CNTF family of cytokines that promotes Müller glial fate (Goureau et al, 2004) and inhibits rod differentiation (Ezzeddine et al, 1997; Rhee et al, 2004; Rhee and Yang, 2010). Indeed, CNTF has been shown to induce the PI3K/Akt signaling cascade in zebrafish retina (Kassen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ciliary neurotrophic factor (CNTF) CNTF exerts numerous effects on the development, differentiation and survival of retinal neurons (Rhee and Yang, 2010). The molecular mechanisms that explain the neuroprotective role of CNTF in the retina include: a direct action on photoreceptors to prevent apoptosis; the stimulation of Müller cells to produce photoreceptor survival factors (Zack, 2000); enhanced synthesis or distribution of glutamate transporters, thereby improving glutamate handling and resulting in less excitotoxic damage to retinal neurons (Escartin et al, 2006); and an induction of metabolic plasticity and increased resistance to metabolic damage (Escartin et al, 2007).…”
Section: Other Trophic Factorsmentioning
confidence: 99%